CD70 as a target in cancer immunotherapy: advances, challenges, and future directions - Wu, Ruchen; Chen, Junze; Wang, Gang; Han, Lulu (Frontiers in Oncology, 2025)
Cancer immunotherapy represents a paradigm shift in oncology by leveraging the immune system to target tumors. The therapeutic efficacy of these approaches depends critically on identifying molecular targets that enhance treatment responses while limiting toxicity. CD70, a TNF family member, has emerged as a promising target due to its overexpression in hematologic malignancies and solid tumors contrasted with restricted expression in healthy tissues. This differential expression profile implies that CD70-directed therapies could achieve tumor-specific cytotoxicity with reduced off-target effects. Nevertheless, key challenges persist, including optimizing delivery systems and elucidating the immunological consequences of CD70 modulation. This review synthesizes recent progress in CD70-targeted immunotherapy, evaluating both its therapeutic potential and current constraints to guide future clinical translation.